Electroanalytical sensing of dyes and colorants - Bessegato, Guilherme G.; Brugnera, Michelle F.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2019)
Color is an important element of the final product of many industries, including the textile, leather, food, cosmetic, pharmaceutical, plastic, and fuel-marking industries. Dyes are complex organic substances with chromophore and auxochromic groups, which can be electrochemically oxidized and/or reduced; this constitutes the basis of their electroanalytical determination. Despite some controversies, dyes pose risks to living organisms, especially after biotransformation, as the metabolites can be more toxic, mutagenic, or carcinogenic than the original dyes. The present work provides a brief overview of the recent progress in electrochemical sensors used for dye detection in diversified matrices. Sensors developed over the recent years are characterized by high sensitivity and selectivity, besides being economically advantageous once they allow the use of little or no clean-up samples in portable and miniaturized systems.
Keywords: azo dyes; detection; determination; electroanalysis; electrochemical